INTERDISCIPLINARY KALOSKAGATHIA PROJECT - Maria REUŢ; Mirela PÎRGHIE; Gabriela GIURANIUC (Annals of the “Ştefan cel Mare” University: Physical Education and Sport Section - The Science and Art of Movement, 2018)
The interdisciplinary KALOSKAGATHIA project was designed for the School Otherwise Week, the disciplines involved in the project are „Physical Education and Sports”, „Nutrition and Health” and „Universal Literature”. The main goal of this project was to provide students a image about an important part of the culture and civilization of the world, the culture and civilization of ancient Greece, the birth of the ancient Olympic spirit of competition in all areas but particularly in sports, literature and the art of the time. The educational objectives of the project were to highlight the achievements of the human spirit from that time, training students in respect of important values, to discover prosperous civilizations, to share information about the concept KALOSKAGATHIA and to awaken the interest, engagement and creativity of the students for this project as an extension of the school syllabus content which unfortunately is not Universal Literature at the level of Technical Colleges, the Physical Training is just another one class per week and the breaches in the nourishment of young people during this period are extremely dangerous. Here are just a few reasons why, we, the teachers involved in this project consider it useful, we intend to continue it in the following years, mentioning the fact that we will do a world tour, next year being among the ancient Rome with his dicton „Mens sana in corpore sano”.